EVALUATION OF ANTIBIOTICS USAGE AMONGST PATIENTS WITH DIABETIC FOOT INFECTION: PROSPECTIVE COHORT STUDY AT ENDOCRINOLOGY CLINIC OF SARDJITO HOSPITAL - Ninisita Sri Hadi; Djoko Wahyono; I Dewa Putu Pramantara (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Diabetic foot is common foot problems in persons with diabetes mellitus. It is suggested that the prevalence of diabetic food cases increase along with the growing number of patients with diabetes mellitus. Diabetic foot commonly appears with manifestation of ulcers, infection, gangrene and Charcoat atrophy. Infection occurs in fifty percent of diabetic foot with ulcers that could lead to amputation if it is not immediately and appropriately treated. Proper antibiotics treatment prevents diabetic foot patient from amputation. This study aimed to understand the pattern of antibiotics usage amongst diabetic foot patients. The appropriateness of antibiotics therapy against current guideline was studied and compared with culture and sensitivity test results. Effectiveness of therapy and patient’s safety was then evaluated. Prospective cohort approach was used to this study. Data of diabetic foot patients was collected during November 2011 – January 2012 at Endocrinology Clinic of Sardjito Hospital. Collected variables included subject characteristics, antibiotics and other medication treatments, visual sign of diabetic foot infection and laboratory test results. Descriptive analysis was then conducted toward all variables. Majority of subjects obtained single therapy of antibiotic when diagnosed with diabetic foot infection. These antibiotics were ciprofloxacin and cefadroxil. Combination of 2 antibiotics were about 31,1%, ciprofloxacin with clindamycin was the most combination in this therapy (37%). About 28.7% of antibiotics therapy was not appropriate with existing guideline. Culture and sensitivity tests strengthen this inappropriateness. It was found that 84.4% of antibiotics therapy was effective. However, there were 5.7% of antibiotic orders that potentially interact negatively with other medication during therapy.Keywords: diabetic food infection, antibiotic, appropriateness, effectiveness, drug  safety